Implementation of Village Minimum Service Standards in Ganra Village, Ganra District, Soppeng District - Guntur, Muhammad; arka, Muh Husni; Sulmiah, Sulmiah (Jurnal Aktor, 2023)
This paper aims to determine the implementation of Village Minimum Service Standards in Ganra Village, Ganra District, Soppeng Regency, this research is based on the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 2 of 2017, namely: a). Provision and dissemination of service information, b). provision of population and land data and information, c). providing a certificate, d). simplification of services, and e). public complaints. This type of research is descriptive qualitative research with data collection techniques, namely observation, interviews and documentation. Data obtained from research results are processed using data analysis techniques, data reduction, data presentation and drawing conclusions. The results of the research show that the implementation of Village Minimum Service Standards in Ganra Village, Ganra District, Soppeng Regency is already in good implementation seen from several indicators, namely: Provision of population and land data and information in Ganra Village is complete and in accordance with Village Minimum Service Standards, provision of letters information is also good with fast service and easy completeness of files in providing certificates, simplification of service is also good by presenting the ATM Pavilion innovation to make it easier and faster to process certificates in Ganra Village. However, it is necessary to optimize the indicators for the provision and dissemination of service information because it is not yet complete in providing service information in Ganra village and also the implementation of community complaints indicators also needs to be optimized because the Ganra village government is not quick enough to respond to community complaints.